Few layered MoS2 grown on pencil graphite: a unique single-step approach to fabricate economical, binder-free electrode for supercapacitor applications. (19th November 2018) - Sha, Rinky; Badhulika, Sushmee
Abstract: While all reports on supercapacitors are based on electrodes that are fabricated either using expensive, complex fabrication techniques or multiple steps based synthesis routes, the current work is the first report of one-step hydrothermally grown MoS2 on pencil graphite electrode (PGE) for ultra-high performance supercapacitor application. Field emission scanning electron microscope images revealed MoS2 micro-flower like structure containing interwoven nanosheets whereas chemical characterizations data confirmed the successful growth of few layered (>4 layers) MoS2 on PGE. The performance of the electrode was optimized using various grades of pencil, and it was found that the areal capacitance of the MoS2 grown on 1H PGE(7178.8 mF cm −2 ) was about 3.4 and 4.1 folds greater than those of the MoS2 grown on 2B, 6H PGE at the same current density respectively. This low cost, binder-free MoS2 based PGE paves a novel way towards the advancement of affordable electrodes for energy storage-conversion and bioanalytical applications.